Identifying behaviour change techniques in 287 randomized controlled trials of audit and feedback interventions targeting practice change among healthcare professionals - Crawshaw, Jacob; Meyer, Carly; Antonopoulou, Vivi; Antony, Jesmin; Grimshaw, Jeremy M.; Ivers, Noah; Konnyu, Kristin; Lacroix, Meagan; Presseau, Justin; Simeoni, Michelle; Yogasingam, Sharlini; Lorencatto, Fabiana (Implementation science : IS, 2023)
Background Audit and feedback (A&F) is among the most widely used implementation strategies, providing healthcare professionals with summaries of their practice performance to prompt behaviour change and optimize care. Wide variability in effectiveness of A&F has spurred efforts to explore why some A&F interventions are more effective than others. Unpacking the variability of the content of A&F interventions in terms of their component behaviours change techniques (BCTs) may help advance our understanding of how A&F works best. This study aimed to systematically specify BCTs in A&F interventions targeting healthcare professional practice change. Methods We conducted a directed content analysis of intervention descriptions in 287 randomized trials included in an ongoing Cochrane systematic review update of A&F interventions (searched up to June 2020). Three trained researchers identified and categorized BCTs in all trial arms (treatment & control/comparator) using the 93-item BCT Taxonomy version 1. The original BCT definitions and examples in the taxonomy were adapted to include A&F-specific decision rules and examples. Two additional BCTs (‘Education (unspecified)’ and ‘Feedback (unspecified)’) were added, such that 95 BCTs were considered for coding. Results In total, 47/95 BCTs (49%) were identified across 360 treatment arms at least once (median = 5.0, IQR = 2.3, range = 1-29). The most common BCTs were ‘Feedback on behaviour’ (present 89% of the time; e.g. feedback on drug prescribing), ‘Instruction on how to perform the behaviour’ (71%; e.g. issuing a clinical guideline), ‘Social comparison’ (52%; e.g. feedback on performance of peers), ‘Credible source’ (41%; e.g. endorsements from respected professional body), and ‘Education (unspecified)’ (31%; e.g. giving a lecture to staff). A total of 130/287 (45%) control/comparator arms contained at least one BCT (median = 2.0, IQR = 3.0, range = 0–15 per arm), of which the most common were identical to those identified in treatment arms. Conclusions A&F interventions to improve healthcare professional practice include a moderate range of BCTs, focusing predominantly on providing behavioural feedback, sharing guidelines, peer comparison data, education, and leveraging credible sources. We encourage the use of our A&F-specific list of BCTs to improve knowledge of what is being delivered in A&F interventions. Our study provides a basis for exploring which BCTs are associated with intervention effectiveness. Trial registrations N/A.